Prevalence and control of hypertension among diabetes patients in hospital universiti sains malaysia, malaysia - Salwa Selim Ibrahim; Ayman Selim I. Bougalambou; Fita Rahmawati; Mohamed Azmi Hassali; Syed Azhar Syed Sulaiman (Indonesian Journal of Pharmacy, 2010)
Hypertension  in  patients  with  type  2  diabetes  mellitus  is  a  prevalent condition that leads to substantial morbidity and mortality. The aim of the study was  to  determine  the  prevalence  of  hypertension  in  type  2  diabetes  attending endocrinology  clinics  at  Hospital  Universiti  Sains  Malaysia  (HUSM),  to  describe antihypertensive  treatment  patterns,  and  to  evaluate  the  target  of  blood pressure  achieved  by  antihypertensive  agents.  The  study  was  a  prospective follow-up  descriptive  study.  Study  conducted  at  diabetic  clinic  outpatient  at HUSM,  Kelantan,  Malaysia  from  January  to  December  2007.  A  total  of  1077 diabetic patients involve in this study. The findings of our study showed that the majority patients type 2 diabetes mellitus 998 (92.7 %) had hypertension. For the  patients  who  were  on  antihypertensive  medications,  254  (23.6  %)  of  them were  on  monotherapy  and  311  (28.9  %),  179  (16.6  %), and  198  (18.4  %) respectively  received  two,  three  and  more  than  three  antihypertensive  agents. The majority of patients 872 (87.4 %) were on angiotensin converting enzyme inhibitors/angiotensin receptor blockers either alone or in combination with other antihypertensive  drugs.   A  number  of  601  (55.8  %)  patients  achieved  blood pressure  targets  ≤  130/80  mm  Hg.   Almost  all  patients  with  hypertension  anddiabetes will require a combination of antihypertensive medications. A number of patients was not achieved blood pressure goals ≤ 130/80 mm Hg. There is still need  to  educate  both  patients  and  health  care  providers  of  importance  of achieving target of blood pressure in order to reduce morbidity and mortality in diabetes mellitus patients.Key words: Hypertension, type 2 diabetes mellitus, hypertension treatment